HUBUNGAN RIWAYAT PAJANAN PESTISIDA SAAT HAMIL DENGAN KEJADIAN BBLR DI KEC. BLADO KAB. BATANG - Jessie Novriani Lentho; Suhartono Suhartono; Dharminto Dharminto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Pesticides exposure during the pregnancy affects the incidence of low birth weight (LBW). Many of studies prove that pesticide has negative effect for the growth of embryo. The aimed of this study was to discover the association between pesticides exposure history during the pregnancy and LBW incidence in Blado Sub-district, Batang Regency. This was a case control study conducted on 50 womans who have been or are still involved in agricultural activities with pregnancy history on 2017. In which 25 of them gaving birth with LBW categorized as case group and the rest of them giving birth with nomal weight categorized as control group. Statistical analysis was done by chi-square test and OR value calculation. There were significant association between the history of agricultural activities involvement during the pregnancy, the intensive involvement on agricultural activities, the work period on agricultural activities, and the completeness of the use of personal protective equipment (PPE) while doing agricultural activities and LBW incidence (p value=0.043; 0.001; 0.004; 0.004). There was no significant association between the intensivity of pesticide exposure with LBW incidence (p value=1.000). The study concluded that doing pesticide-related agricultural activities during pregnancy with incomplete PPE usage, and the long work period in agricultural activities have association with LBW incidence.